2021
DOI: 10.48550/arxiv.2101.10580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toward Personalized Affect-Aware Socially Assistive Robot Tutors in Long-Term Interventions for Children with Autism

Abstract: Affect-aware socially assistive robotics (SAR) has shown great potential for augmenting interventions for children with autism spectrum disorders (ASD). However, current SAR cannot yet perceive the unique and diverse set of atypical cognitive-affective behaviors from children with ASD in an automatic and personalized fashion in long-term (multi-session) real-world interactions. To bridge this gap, this work designed and validated personalized models of arousal and valence for children with ASD using a multi-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…1) showed that the transfer learning algorithm can improve the accuracy of facial emotional classification based on a generic classifier and a personalized classifier (see (a), (b) in Fig. 1 that the mean accuracy in middle is higher than both end), and this result is consistent with the experiment in [22,23,26]. Now we are requesting the permission of accessing an emotional dataset of children with ASD to test the accuracy of emotional classifier on children with ASD.…”
Section: Current Work Done So Farsupporting
confidence: 69%
See 2 more Smart Citations
“…1) showed that the transfer learning algorithm can improve the accuracy of facial emotional classification based on a generic classifier and a personalized classifier (see (a), (b) in Fig. 1 that the mean accuracy in middle is higher than both end), and this result is consistent with the experiment in [22,23,26]. Now we are requesting the permission of accessing an emotional dataset of children with ASD to test the accuracy of emotional classifier on children with ASD.…”
Section: Current Work Done So Farsupporting
confidence: 69%
“…However, the relationship between emotion and metacognitive monitoring accuracy of children with ASD is still emerging. The Facial Emotion Expression (FEE) of children with ASD can not be recognised with a reliable accuracy [3,22,26,31], because children with ASD have unique and impaired emotion expressions [2,28]. Thus our research project aims to fill the following gaps:…”
Section: Research Topicmentioning
confidence: 99%
See 1 more Smart Citation
“…Algorithms that take more time to train their model and, consequently, present more computational costs are also used to address this issue. Machine learning algorithms with supervised domain adaptation (s-DA) to afford personalized models are examples of this kind of knowledge base for decision-making [18]. Evaluations of such methods on the effects of personalization on a long-term multimodal dataset showed that their outcomes outperformed non-personalized, individualized and generic model baselines in both individual sessions and also in the average of all sessions.…”
Section: Related Workmentioning
confidence: 99%
“…As shown in Figure 1(B), we plan to develop the SAR tutor with a touchscreen tablet that will serve as a shared collaborative space for the child and robot. Each participant will take part in a first pilot session, whose multimodal data will be annotated and used to pre-train personalized affective models of arousal and valence using supervised domain adaptation we have already validated in our previous work [26]. Using real-time predictions of arousal and valence, we plan to apply an affective reinforcement learning approach in order to personalize the robot's responses to keep the child engaged in the ACT interventions.…”
Section: Personalized Sar Intervention Systemmentioning
confidence: 99%